Methylphenidate can help reduce weight, appetite, and food intake—a narrative review of adults’ anthropometric changes and feeding behaviors - Vedrenne-Gutiérrez, Fernand; Yu, Sion; Olivé-Madrigal, Anna; Fuchs-Tarlovsky, Vanessa (Frontiers in Nutrition, 2024)
Introduction Obesity constitutes a complex global health that carries several comorbidities that include cardiovascular disease, diabetes, and cancer. Current treatments, such as lifestyle modifications and bariatric surgery, are often difficult to implement or carry risks, creating a need for alternative approaches. Methylphenidate (MPH), a drug commonly used to treat Attention Deficit and Hyperactivity Disorder (ADHD), has shown potential in regulating dopamine levels to modulate appetite and feeding behaviors. Methods This narrative review evaluated the effect of MPH in reducing food intake, body weight, and anthropometric indicators in adults with obesity or overweight. Using the PICO method, 39 studies were selected, including 14 randomized controlled trials and 3 observational studies. Results MPH canblead to modest weight loss of 1–2% and significant appetite suppression, with stronger effects observed in women, who reported greater reductions in appetite and food cravings. Studies could remain underpowered to detect consistent effects in men. Discussion Even if these results suggest MPH could be an option for treating obesity, concerns regarding its safety profile and long-term efficacy persist. This review underscores the need for further investigation to confirm MPH’s therapeutic potential, particularly through studies that address gender-specific responses and evaluate its sustainability as a weight management tool.